2001
DOI: 10.1097/00001756-200108080-00025
|View full text |Cite
|
Sign up to set email alerts
|

The effects of single-trial averaging upon the spatial extent of fMRI activation

Abstract: We examined effects of trial averaging upon spatial extent, spatial topography, and temporal properties of fMRI activation. Two subjects participated in an event-related visual stimulation design. There was an exponential relation between number of trials and spatial extent, such that additional trials identi®ed, on average, a constant proportion of the remaining voxels. At values typical of fMRI experimentation (e.g. 50 trials) only about 50% of eventually active voxels were signi®cant; asymptotic values were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
47
0

Year Published

2002
2002
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(52 citation statements)
references
References 13 publications
5
47
0
Order By: Relevance
“…the spatial extent of activation increased monotonically and failed to asymptote even after 22 scans (Saad et al, 2003). Huettel and McCarthy have reported a similar result in an event-related task (Huettel and McCarthy, 2001). It was found that at a number of events typical of fMRI experiments (i.e., 50 trials), only 50% of the eventually active voxels were found to show a significant effect.…”
Section: Introductionmentioning
confidence: 64%
See 2 more Smart Citations
“…the spatial extent of activation increased monotonically and failed to asymptote even after 22 scans (Saad et al, 2003). Huettel and McCarthy have reported a similar result in an event-related task (Huettel and McCarthy, 2001). It was found that at a number of events typical of fMRI experiments (i.e., 50 trials), only 50% of the eventually active voxels were found to show a significant effect.…”
Section: Introductionmentioning
confidence: 64%
“…These activation maps were then thresholded and the number of active voxels in the ROIs derived above was counted. The correlation analysis maps were thresholded at P < 0.001 (t > 3.88341) as in Huettel and McCarthy (2001). The GLM analysis activation maps were also thresholded at P < 0.001 (z = 3.1).…”
Section: Permutation Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies included twenty subjects each and were conducted to find an appropriate experimental design for the present fMRI study. Huettel and McCarthy, 2001). Furthermore, a third pilot study was conducted to test whether background colors will get associated with the emotional valence of the facial expression with which they were combined during the first experimental run.…”
Section: Pilot Studiesmentioning
confidence: 99%
“…The standard deviation of the noise was varied between 3.2 and 4 leading to signal-to-noise ratios (SNR, ratio of the mean of the MR signal to the standard deviation of the noise [Huettel and McCarthy, 2001b]) of approximately 210, 190, and 170 in three different variations of each simulated time-series. All resulting simulated time-series data were analyzed using general linear model with FIR predictors, identical to analysis of the empirical data.…”
Section: Simulated Experimentsmentioning
confidence: 99%